Nouvelles formes de gouvernance dans le domaine de l’eau. Apports et limites de la coopération décentralisée dans les pays en développement - Raoudha Makkaoui; Jean Luc Dubois (Développement Durable et Territoires)
Our paper builds on this issue of decentralized cooperation in the field of water management. Cooperation between decentralized entities in order to ensure the access to safe drinking water for all now constitutes in many places a preferred water governance option. Therefore, in the first part, we will provide an overview of the current difficulties encountered by the various forms of water management in developing countries, showing the solutions that they successively brought to specific issues (access for all, cost reduction, priority needs). In the second part, we will address the particular case of decentralized cooperation between the General Council of Seine-Saint-Denis in the suburbs of Paris, France, in partnership with the city of Figuig in Morocco. We review the insights and limits of such processes that refer to the people’s capabilities, at both individual and collective levels, in order to ensure “social sustainability”.